Analyze of SEIR dengue infectious transmission model with vaccination - Chamnan, Anusit; Pongsumpun, Puntani (My University, 2020)
Dengue infection is caused by dengue virus. The virus live in the Aedes mosquitoes. Dengue fever (DF) is caused by the dengue virus. They have four serotypes such that DEN-1, DEN-2, DEN-3, and DEN-4. The disease is transmitted from the biting of mosquito through the mosquito's saliva. We focus on the mathematical model of dengue disease with vaccination before the first serotypes infections of the dengue virus and considered the recurrent infection and death from infection. We used SEIR model (Susceptible-Exposed-Infected-Recovered) for the human population and SI for vector population. This is used to examine the dynamics of the disease. We analyzed the stability of the model by using dynamic analysis. The equilibrium states and the reproductive number of our model are found. The numerical simulations are used for compare the parameters that affect this model, result, and conclusion are presented.
Keywords: dengue virus; mathematical model; vaccination